Sosialisasi Perijinan dan Sertifikasi Halal Menuju Keberlanjutan UMKM di Desa Pekasiran, Kecamatan Batur, Kabupaten Banjarnegara, Jawa Tengah - Dhian Andanarini Minar Savitri; Sugiharti Sugiharti; Emi Wardati; Tri Sumiyanti; Shofiyana Shofiyana (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Pekasiran Village, Batur District, Banjarnegara Regency, Central Java, have begun to experience an increase in both the number of MSMEs and the types of businesses they carry out. This increase in the number has not been followed by the implementation of permits that must be carried out by business actors. The majority of MSMEs engaged in the food sector have indeed taken care of permits such as PIRT, however, there are still many who have not done so. This licensing socialization was provided while also assisting MSME actors to take care of permits such as making NIB (Business Identification Number), and also taking care of Halal certification. The results of the community service show that MSME actors are open to the importance of taking care of permits for their businesses. The licensing assistance process still needs to be carried out continuously and support from the local government is also needed.